Economic integration: the existence of Cointegration between Brazilian and Mexican GDPs - Cassano, Dr., Francisco Américo; Santos, Diego Henrique Cotrim; Pinto, Carlos Alberto Cuenca; Ciarmoli, Caiê Betareli; Teodoro, Rafael Tsopanoglou; Pelegrina, Renan (Revista de Negócios, 2016)
The process of globalization has expanded international relations and forced companies and countries to formalize a series of strategies to participate competitively in this process. Economic integration is one of these strategies and focuses on uniting efforts of economies with common economic and social interests, by promoting trade, stimulating markets and making the economic relations between these countries more productive and efficient. Considering the hypothesis that from the economic integration there was no relationship between the Brazilian and Mexican GDP, the main focus of this study is to evaluate and register the importance of economic integration for the economic growth of the countries. To analyze the GDP growth of Brazil and Mexico, before and after the integration in their respective blocks, it was applied the Cointegration tests model developed by Engle and Granger. The results obtained allowed to conclude that for the period prior to the integration there was no relationship between the Brazilian and Mexican GDP growth, and, for the period after the GDPs kept relationship between them.